Canadian hand dermatitis management guidelines - Lynde, Charles; Guenther, Lyn; Diepgen, Thomas L.; Sasseville, Denis; Poulin, Yves; Gulliver, Wayne; Agner, Tove; Barber, Kirk; Bissonnette, Robert; Ho, Vincent; Shear, Neil H.; Toole, Jack (Journal of cutaneous medicine and surgery, 2010)
Hand dermatitis (HD) is one of the most common skin conditions; however, it is not a homogeneous disease entity. The severity of HD may range from very mild cases to severe chronic forms, which may result in prolonged disability and, occasionally, refractory HD. Chronic hand dermatitis (CHD) is associated with a high health- economic burden and significant loss of quality of life. Although numerous treatment options are available, the management of CHD is often difficult and unsatisfactory. There is a paucity of well-designed, randomized, controlled clinical trials in support of the efficacy of established treatment modalities.Conclusion:These guidelines cover the epidemiology, burden, quality of life, etiology, diagnosis, classification, and prevention of HD and provide guidance on management using an approach that is as evidence based as possible.
Gesehen am 20.04.2023